Coupled biomass (lignin) gasification and iron ore reduction: A novel approach for biomass conversion and application. (1st December 2017) - Wei, Rufei; Feng, Shanghuan; Long, Hongming; Li, Jiaxin; Yuan, Zhongshun; Cang, Daqiang; Xu, Chunbao (Charles)
Abstract: Aiming at a novel application of biomass, coupled biomass gasification and iron ore reduction was investigated and demonstrated in this work through pyrolysis/gasification of iron ore–lignin pellets (ILP) at 1093–1333 K. The solid, liquid and gaseous products were analyzed by XRD, SEM, chemical analysis, GC-MS, GC and TG-FTIR. Direct reduction iron (DRI) and gaseous products (CO, H2 and CH4 ) were produced in the process. The metallization degree of the iron ore and CO content of the gaseous products increased with increasing the reaction temperature, as expected. The gas yield from the experiments with ILP was much higher than that from the tests with lignin pellets (LP) at 1173–1333 K, owing mainly to the iron ore reduction producing a larger amount of CO. Whereas, the yields of oil and char in the ILP reduction process were found to be much lower than those from the tests with lignin alone, due to the conversion of oil and char products into gaseous products catalyzed by the iron oxide and metallic iron. Thus, in pyrolysis/gasification of ILP the presence of lignin provided reducing agents for reduction of iron oxide, whereas the presence of iron oxide/metallic iron provided an oxidant/catalyst for biomass gasification. Graphical abstract: Highlights: Coupled biomass gasification and iron ore reduction by pyrolysis of iron ore–biomass pellets. Iron oxide/metallic iron provided an oxidant/catalyst for biomass gasification. Biomass provided reducing agents for reduction of iron oxide.